City Diplomacy as a Mechanism of Multi-Level Solidarity and Support for Ukraine: A Study of the Changes Following the 2022 Russian Invasion - Natalia Matiaszczyk (Journal of Eurasian Studies)
The full-scale Russian invasion of Ukraine in 2022 changed the situation in Europe, impacting various aspects, such as politics, security, and international relations. It also underscored the significance of local authorities, particularly cities, in responding to and addressing the consequences of the crisis. The paper answers the questions on the impact of the Russian invasion on the international partnerships of Ukrainian cities, the role of city diplomacy in promoting solidarity and support for Ukraine, and the dynamics of multi-level cooperation in supporting Ukraine during the war. This research was based on a survey sent to 56 Ukrainian cities, of which 70% of them responded. The findings indicate that almost 90% of Ukrainian cities receive diverse forms of support from foreign partners, and two-thirds of them engage in forging new partnerships. Moreover, through many multi-level initiatives, they contribute significantly to the dynamic interplay between local, national, and international levels of governments. These results highlight the noteworthy role of cities in international relations as actors in times of war.